Moral education and literature: the contribution of utopias and tales - Giuseppe Mari (Ignatianum University Press, 2018)
Since the beginning of Western culture utopias and tales have been involved within moral education. The contribution aims to make clear that this kind of literature is suitable from the pedagogical point of view principally because of the symbolic communicative style. It is important to be aware of the difference between ancient and modern utopias too.